2021
DOI: 10.1039/d1py00333j
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of chain transfer via a restricted rotation effect of dibenzosuberyl substituents in polymerization catalysis

Abstract: The introduction of bulky ortho-steric substituents into α-diimine Ni(II) and Pd(II) species has been often used as an effective strategy to retard the chain transfer in olefin polymerization. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Similar to the α‐diimine Pd(II) system, 39–44 iminopyridine Pd(II) catalysts can also be used for the copolymerization of ethene and polar monomers. In this contribution, the newly synthesized iminopyridine Pd(II) catalysts were also tested for the copolymerization of ethene with MA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the α‐diimine Pd(II) system, 39–44 iminopyridine Pd(II) catalysts can also be used for the copolymerization of ethene and polar monomers. In this contribution, the newly synthesized iminopyridine Pd(II) catalysts were also tested for the copolymerization of ethene with MA.…”
Section: Resultsmentioning
confidence: 99%
“…This further indicates that the Pd(II) species can carry out more in-depth chain isomerization and give a more topological molecular structure than the corresponding Ni(II) species. Similar to the α-diimine Pd(II) system, [39][40][41][42][43][44] iminopyridine Pd(II) catalysts can also be used for the copolymerization of ethene and polar monomers. In this contribution, the newly synthesized iminopyridine Pd(II) catalysts were also tested for the copolymerization of ethene with MA.…”
Section: Ethene (Co)oligomerization Catalyzed By Pd(ii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that the remote nonconjugated electron effect significantly affects the polymerization activity, molecular weight, and branching density of the polyolefins in the α-diimine system. , However, in the iminopyridine Ni­(II) system, the remote nonconjugated electronic substituents (H, Me, F, Cl) exhibited no significant effect on the polymerization parameters (Figure ). Our recent work has revealed a rotation-restricted dibenzosuberyl substituent can effectively retard the chain transfer during ethylene polymerization, thus, leading to a high molecular weight. ,,, The dibenzosuberyl substituent in the iminopyridine Ni­(II) system demonstrated a significant impact on the molecular weight of the generated polyethylene. Compared with the diarylmethyl catalysts Ni1 – Ni4 , the one with the dibenzosuberyl substituent ( Ni5 ) generated an order of magnitude higher molecular weight (Figure b), thus, transforming the system from ethylene oligomerization to ethylene polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent work has revealed a rotation-restricted dibenzosuberyl substituent can effectively retard the chain transfer during ethylene polymerization, thus, leading to a high molecular weight. 46,47,53,54 The dibenzosuberyl substituent in the iminopyridine Ni(II) system demonstrated a significant impact on the molecular weight of the generated polyethylene.…”
Section: Introductionmentioning
confidence: 99%